Understanding human resources management strategy in implementing good government practice: what research evidence say - Hidir, Achmad; Zunaidi, Arif; Pattiasina, Petrus Jacob (International research journal of management, IT and social sciences, 2021)
Understanding human resource development strategies in good governance service practices are essential. For this reason, we have reviewed several study pieces of evidence to add to the enrichment of our study. The reading sources we are looking for are data-based sources from Google scholars, ERIC publications, and other literature sources. Furthermore, we take the analysis stage by involving the coding system, evaluation, data extract, in-depth interpretation, and drawing conclusions that are valid findings and high reliability because these findings have answered the questions and danced the hypothesis of this study. We depend on secondary data and descriptive qualitative study designs. Based on the discussion of the findings data, we can conclude that the HR governance strategy working in public service organizations is not only required for superior competence, technical skills, and mastery of the underlying laws and regulations, but they are state apparatuses that are even more crucial in shaping mental and behavioral professional, friendly in nurturing, honest, sympathetic, wise, intelligent, and highly responsible.